LEGAL CONSEQUENCES FOR OFFENDERS WHO VOTE MORE THAN ONCE IN THE CRIMINAL ACT OF THE GENERAL ELECTION (ELECTION) RULING STUDY NO. 132/PID.SUS/2019/PN.GST: AKIBAT HUKUM BAGI PELAKU YANG MEMBERIKAN SUARA LEBIH DARI SATU KALI DALAM TINDAK PIDANA PEMILIHAN UMUM (PEMILU) STUDI PUTUSAN NO. 132/PID.SUS/2019/PN.GST - Murtiyanto, Herlan (UPMI Proceeding Series, 2023)
Article 156 of law Number 7 of 2017 concerning General Elections states that "everyone who intentionally casts his/her vote more than once at one polling station (TPS)/Overseas polling station (TPLSN) or more, shall be subject to a criminal sanction. with a maximum imprisonment of 18 (eighteen) months and a maximum fine of Rp.18,000,000.00 (eighteen million rupiah). The writing of this article aims to explain the factors in the occurrence of a criminal act of voting more than once in a general election crime. This research uses normative juridical research. According to the author's analysis, someone commits an election crime, one of which is voting more than once in a general election, there are several factors such as the influence of money politics, low legal knowledge, and still registered voters at several polling stations. And the defendant in this decision committed the crime to get more votes because the defendant is a legislative candidate from the Indonesian Unity Justice Party (PKPI). Settlement of the crime of voting more than once in a criminal act of general election is carried out by Article 516 of Law Number 7 of 2017 concerning General Elections. Efforts to prevent these crimes are to carry out socialization efforts to the whole community, to make improvements to voter data by the organizers of the general election.